(untitled) (Journal of Current and Advance Medical Research, 2023)
Background: Neglected elbow dislocation often results in contracture and functional impairments. Surgical treatment is challenging because of the accompanying triceps retraction. Objectives: The purpose of the present study was to surgical outcomes of treating the neglected dislocations of elbow joint using the posterior approach. Methodology: This was a non-randomized clinical trial over a three years period from January 2017 to December 2019. All the patients who were presented with a neglected elbow dislocation which was older than 21 days were selected as study population. The average follow-up was 18 months with the range 12 to 24 months after surgical procedure. Results: A total number of 10 patients were treated with an average age of 24.6±10.52 years (range 14 to 48 years). The dislocations were 6.6±3.69 months old on average (range 2 to 12months). Average elbow flexion was 46.5±26.04(15º-90º) and the extension deficit was 14.5±19.58(0º-50º) before the surgery. A paratricepital approach was used in all patients. In 7 patients, the dislocation was reduced without triceps lengthening. In 3 patients, a V-Y plasty of the triceps muscle was required. The improvements in the overall range of motion were statistically significant. Average elbow flexion was118±11.35 (100º-130º) and extension deficit was 20.5±15.17. Complications included one case of ulnar nerve paresis, which subsided within two months, and one case of superficial infection. Conclusion: In conclusion the functional improvement in neglected elbow dislocations is outstanding. Journal of Current and Advance Medical Research, July 2022;9(2):63-68